Glycine amidinotransferase (GATM), renal Fanconi syndrome, and kidney failure - Reichold, M; Klootwijk, ED; Reinders, J; Otto, EA; Milani, M; Broeker, C; Laing, C; Wiesner, J; Devi, S; Zhou, W; Schmitt, R; Tegtmeier, I; et al. (American Society of Nephrology, 2018)
Background For many patients with kidney failure, the cause and underlying defect remain unknown. Here, we describe a novel mechanism of a genetic order characterized by renal Fanconi syndrome and kidney failure.Methods We clinically and genetically characterized members of five families with autosomal dominant renal Fanconi syndrome and kidney failure. We performed genome-wide linkage analysis, sequencing, and expression studies in kidney biopsy specimens and renal cells along with knockout mouse studies and evaluations of mitochondrial morphology and function. Structural studies examined the effects of recognized mutations.Results The renal disease in these patients resulted from monoallelic mutations in the gene encoding glycine amidinotransferase (GATM), a renal proximal tubular enzyme in the creatine biosynthetic pathway that is otherwise associated with a recessive disorder of creatine deficiency. In silico analysis showed that the particular GATM mutations, identified in 28 members of the five families, create an additional interaction interface within the GATM protein and likely cause the linear aggregation of GATM observed in patient biopsy specimens and cultured proximal tubule cells. GATM aggregates-containing mitochondria were elongated and associated with increased ROS production, activation of the NLRP3 inflammasome, enhanced expression of the profibrotic cytokine IL-18, and increased cell death.Conclusions In this novel genetic disorder, fully penetrant heterozygous missense mutations in GATM trigger intramitochondrial fibrillary deposition of GATM and lead to elongated and abnormal mitochondria. We speculate that this renal proximal tubular mitochondrial pathology initiates a response from the inflammasome, with subsequent development of kidney fibrosis.